How faithfully does intramembranous bone regeneration recapitulate embryonic skeletal development?. Issue 3 (9th September 2020) - Ko, Frank C.; Sumner, D. Rick
Abstract: Postnatal intramembranous bone regeneration plays an important role during a wide variety of musculoskeletal regeneration processes such as fracture healing, joint replacement and dental implant surgery, distraction osteogenesis, stress fracture healing, and repair of skeletal defects caused by trauma or resection of tumors. The molecular basis of intramembranous bone regeneration has been interrogated using rodent models of most of these conditions. These studies reveal that signaling pathways such as Wnt, TGFβ/BMP, FGF, VEGF, and Notch are invoked, reminiscent of embryonic development of membranous bone. Discoveries of several skeletal stem cell/progenitor populations using mouse genetic models also reveal the potential sources of postnatal intramembranous bone regeneration. The purpose of this review is to compare the underlying molecular signals and progenitor cells that characterize embryonic development of membranous bone and postnatal intramembranous bone regeneration. Key Findings: Review of postnatal intramembranous bone regeneration in the context of embryonic membranous bone development